Artistic and Aesthetic Searches in the Stories of Almaz Myrzakhmet (Eurasian Journal of Philology Science and Education, 2025)
The article examines the collection of stories “Déjà vu” by the writer Almaz Myrzakhmet. The analysis of the style of individual stories by the writer revealed his artistic searches. The analysis of the character system was focused on issues of demography, criticism of the lives of single mothers and the fate of such characters as the actress in the story “Actress” and Bapakai in the story “Bapakai”. From the history of literature it is known that in Kazakh literature several stories and novellas were written about the December Uprising of 1986, starting with the small genre. In the story “Déjà vu”, named after the collection, we get acquainted with the “peers of independence” named Kairat, Yerbol, Sabira and Lyazzat, named so as to forever remember the names of the heroes of December. The educational value of the conversation was emphasized by the pride of the youth of Astana, Ust-Kamenogorsk and Almaty, who met in Astana on the eve of the thirtieth anniversary of independence. The main achievement of the work is the formation of a sense of patriotism, selflessness and respect for the heroes of December in young people. It was established that the characters of the writer's stories, different in content and form, are taken from real life and reflect our past, present and future through real life. If psychologism in the analyzed stories is reflected in the flow of consciousness in the story “Self-portrait”, which is based on the unconscious, and in the coloring of the character in the story “At the railroad crossing”, then the stories “A Writer's Note”, “Fire”, “Pillar” are based on mysticism. These stories contain elements of the thriller and horror genres, as well as a description of extremely frightening events associated with ghosts and phenomena. “Eldorado”, consisting of two or three sentences, is an example of a mini-story, which is currently widely recognized in world literature and has begun to take root in Kazakh literature. Due to the limited time in the information age, the author masters writing techniques as concisely as possible and transfers them to national literature. The writer, enriching national literature with urban prose, demonstrated his creative searches in creating new experiments, while maintaining the continuity of tradition.Key words: prose, story, mini-story, psychology, mysticism, style, artistic search.